The Gender of Modernism A Critical Anthology - Scott, Bonnie (Indiana University Press, 1990)
"This is the book we've been waiting for: a distinguished collection that demonstrates how revisions of Modernist definitions might proceed. . . . The Gender of Modernism . . . will be nothing less than an absolutely necessary text for Modernist studies." -Shari Benstock "Scott and her contributing editors . . . effectively [bring] together the issues of gender and modernism into a volume recommended for reference and classroom use." -James Joyce Literary Supplement " . . . a treasure trove for anyone interested in the literature and history of modern times." -Susan Gubar Authors included are: Djuna Barnes, Willa Cather, Nancy Cunard, H.D., T.S. Eliot, Jessie Redmond Fauset, Zora Neale Hurston, James Joyce, Nella Larsen, D.H. Lawrence, Mina Loy, Rose Macaulay, Hugh MacDiarmid, Katherine Mansfield, Charlotte Mew, Marianne Moore, Ezra Pound, Jean Rhys, Dorothy Richardson, May Sinclair, Gertrude Stein, Sylvia Townsend Warner, Rebecca West, Antonia White, Anna Wickham, and Virginia Woolf.